2011
DOI: 10.1002/eej.21136
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated current in low‐density polyethylene/MgO nanocomposite. On the mechanism of its superior dielectric properties

Abstract: SUMMARYPolymer nanocomposites are attracting attention as emerging insulating materials. We measured the thermally stimulated depolarization current (TSDC) in low-density polyethylene (LDPE)/MgO nanocomposites while varying measuring such parameters as the temperature increase rate and the intensity of the applied electric field. A TSDC peak that spreads over a wide temperature range from 0 °C to 60°C was observed in all samples. As the amount of MgO nanofiller increases, the TSDC peak height decreases. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…[10]. Results of TSC measurements suggested that such localized states can be around 1.6-2.0 eV away from extended states [7,30,31]. The numerical model proposed in this work considering the second trapping center at the energy depth of 1.5 eV gives a satisfactory explanation for the observation of ADC at a lower temperature (60 • C) for the nanocomposite as compared to the pure LDPE.…”
Section: Impact Of Nanofillers On Electrical Conductionmentioning
confidence: 54%
“…[10]. Results of TSC measurements suggested that such localized states can be around 1.6-2.0 eV away from extended states [7,30,31]. The numerical model proposed in this work considering the second trapping center at the energy depth of 1.5 eV gives a satisfactory explanation for the observation of ADC at a lower temperature (60 • C) for the nanocomposite as compared to the pure LDPE.…”
Section: Impact Of Nanofillers On Electrical Conductionmentioning
confidence: 54%
“…Thus for LDPE/MgO nanocomposite, the trap depth may be 1–5 eV with the highest level corresponding to the applied field strength of ~200 kV/mm. Further, the trap depth of ~2 eV has been detected in LDPE/MgO nanocomposite by analyzing results of thermally stimulated currents and the origin of these deep traps have been explained by the effect of nanofillers [25]. Based on these findings, the trap depth should be set higher than that for unfilled LDPE.…”
Section: Results Of the Simulations And Discussionmentioning
confidence: 99%
“…There have been a number of studies of the mechanisms underlying the low space charge accumulation and high volume resistivity. For example, Ishimoto and colleagues measured thermally stimulated currents in polyethylene‐based nanocomposites and pointed out the possibility that the nanoparticles formed new trap levels, thus strongly constraining the space charge . Maezawa and colleagues proposed a new mechanism in which nanoparticles act as deep trap sites by forming potential wells .…”
Section: Long‐term DC Characteristics Of Dc‐xlpe Insulationmentioning
confidence: 99%
“…. A life exponent n=15 was chosen on the basis of the V − t characteristic of DC‐XLPE cable . The impulse withstand voltage Vimp (as typified by the lightning impulse voltage) was calculated by Eq.…”
Section: Cable Structure and Insulation Designmentioning
confidence: 99%